The Effect of Interpersonal Relationships, Time Management, Work Efficiency, Role Modeling, and Job Burnout on Employee Performance at Cafe Marowa Batam - Dea Ananda; Andika Nugraha; Muhammad Yusuf (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study is motivated by the need to maintain employee performance at Cafe Marowa Batam amid the dynamic demands of the food and beverage service industry, which requires fast coordination and consistent service quality. The objective of this research is to analyze the effects of interpersonal relationships, time management, work efficiency, role modeling, and job burnout on employee performance, both partially and simultaneously. The study employed a quantitative approach using primary data collected through questionnaires distributed to 40 employees. The data were analyzed using multiple linear regression with SPSS version 28.0. The partial test results indicate that interpersonal relationships, time management, work efficiency, and role modeling have positive and significant effects on employee performance. In contrast, job burnout has a significant negative effect on employee performance. Simultaneously, all independent variables significantly influence employee performance. The coefficient of determination shows that the model explains 92.7 percent of the variation in employee performance, indicating strong explanatory power. The results also suggest that work efficiency provides the strongest relative contribution among the predictors, while burnout consistently reduces performance outcomes. Overall, the findings highlight that employee performance in a café setting is shaped by both operational capabilities and workplace dynamics, including leadership example and employee well-being. In practical terms, managers should strengthen teamwork and communication routines, improve task prioritization and scheduling, standardize efficient work procedures, and reinforce leaders’ exemplary behavior. In parallel, preventive actions to reduce burnout (such as balanced workloads, adequate rest breaks, and job variation) are important to sustain performance over time. These findings suggest that improving employee performance at Cafe Marowa Batam requires an integrated approach that emphasizes effective interpersonal relationships, proper time management, efficient work practices, exemplary leadership behavior, and effective management of job burnout.